2002
DOI: 10.1021/jf0114637
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity of Honeys from Various Floral Sources Based on the Determination of Oxygen Radical Absorbance Capacity and Inhibition of in Vitro Lipoprotein Oxidation in Human Serum Samples

Abstract: Honeys from seven different floral sources were analyzed for in vitro antioxidant capacity and total phenolic content. Antioxidant capacity was measured by the oxygen radical absorbance capacity (ORAC) assay and by monitoring the formation of conjugated dienes as an index of the inhibition of copper-catalyzed serum lipoprotein oxidation. ORAC values ranged from 3.1 to 16.3 micromol Trolox equivalent/g honey. The darkest colored honeys, such as buckwheat honey, had the highest ORAC values. A linear correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
345
3
15

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(391 citation statements)
references
References 39 publications
28
345
3
15
Order By: Relevance
“…Raw Millefiori honey, for example, is packed full of antioxidants [86][87][88]. In addition to the direct contribution to the radical scavenging activity, the polyphenolic content also influences the honey color.…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw Millefiori honey, for example, is packed full of antioxidants [86][87][88]. In addition to the direct contribution to the radical scavenging activity, the polyphenolic content also influences the honey color.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Conjugated systems of double bonds, such as those present in flavonoids, terpenes, isoprene units and long chain phenolic acids present in honey, constitute chromophores that absorb photons of visible light giving rise to colors ranging from yellow to brown. Several reports point out the positive and highly significant correlation between honey color, phenolic content and antioxidant activity [85,87,88].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Flavonoids are known to inhibit lipid oxidation through both metal chelating and free radical scavenging mechanisms, whereas phenolic acids act as antioxidants via free radical trapping mechanisms [30].…”
Section: Fluorimetric Assaymentioning
confidence: 99%
“…Honey contains significant antioxidant activities as well as choline and acetylcholine which are essential for brain function and as neurotransmitters [25][26][27][28][29]. Recent studies reported that honey is one of the natural preventive therapies of both cognitive decline and dementia, as it possesses antioxidant properties and it enhances the brain's cholinergic system [30].…”
Section: Introductionmentioning
confidence: 99%